Pelatihan Pembuatan Abon Tempe Sebagai Upaya Diversifikasi Pangan Di Desa Rambigundam - Robiatus Siddiqiah; Wahyu Andika Putra; Elok Dwi Sofyaningrum; Chintya Dewi Puspita Sari; Alfian Falakhi Sahana Putra; Vivi Ilmil Mufidah; Moh. Zainal; Dewi Denanda; Siti Umi Hanik; Prislia Mudita Oktasari; Fahmi Ulum; Aisyatul Jannah; Hayisul Iman Sukron; Putri Yolanda Maharani; Diah Aprilia Putri; Wulan Vatmasari; Shandyka Yudha Febrian Prasetyo (CV. ITTC INDONESIA, 2024)
The Tempe Floss Making Training Program in Rambigundam Village is an initiative to increase the economic value of the abundant tempe in the area. Through this training, the community of Gayam Hamlet is taught how to process tempe into floss, a value-added product that has the potential to increase local income. This program not only enhances skills in tempe processing but also promotes food diversification and opens up new business opportunities for the community. The training method includes direct demonstrations and education on food diversification. The results of the training show an increase in community knowledge and skills, with some participants starting to develop tempe floss businesses independently. The success of this program is supported by community enthusiasm and support from village officials. Challenges faced include limited training time and product marketing constraints. For program sustainability, assistance in marketing and product development is needed, as well as collaboration with local government. This program is expected to be a concrete step in improving the economy and nutrition of the community in Rambigundam Village.